Correction: The sound of trustworthiness: Acoustic-based modulation of perceived voice personality. - Pascal Belin; Bibi Boehme; Phil McAleer (PLoS ONE, 2019)
[This corrects the article DOI: 10.1371/journal.pone.0185651.].